The Javanese Lunar Calendar’s Effect on Indonesian Stock Returns - Robiyanto, Robiyanto; Siti Puryandani (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
It is very possible for an investor to take a decision based on superstitions and common beliefs. Actually, Indonesia has a specific calendar system called the Javanese lunar calendar. The Javanese calendar contains several special days because of their sacred characteristics such as “Kamis Wage” (Thursday Wage) and “Jum’at Kliwon” (Friday Kliwon). The day of Friday Kliwon is often considered to be the most frightening which is similar to Friday the Thirteenth in Western culture. This study tried to scrutinize the impact of those sacred days on Indonesian stock returns. By applying GARCH-M, the finding shows that the Javanese lunar calendar does not have any impact on the Indonesian stock returns, but does affect the investors’ risk aversion level. This study has proven that, in terms of risk aversion, investors’ behavior in Indonesia is influenced by superstition.